Gloeosporiocide, a new antifungal cyclic peptide from Streptomyces morookaense AM25 isolated from the Amazon bulk soil. Issue 14 (7th August 2019) - Vicente dos Reis, Gislâine; Abraham, Wolf-Rainer; Grigoletto, Diana Fortkamp; de Campos, Jessica Bueno; Marcon, Joelma; da Silva, Jose Antonio; Quecine, Maria Carolina; de Azevedo, João Lúcio; Ferreira, Antonio Gilberto; de Lira, Simone Possedente
ABSTRACT: Actinobacteria are known by their ability to produce several antimicrobial compounds of biotechnological interest. Thus, in this study, we isolated and identified by partial 16S RNA sequencing ∼100 actinobacteria isolates from guarana ( Paullinia cupana ) bulk soil. Besides, we isolated from the actinobacteria Streptomyces morookaense AM25 a novel cyclic peptide, named gloeosporiocide, molecular formula C44 H48 N11 O7 S3 (calculated 938.2901), and characterized by the presence of cyclized cysteins to form three thiazols. The novel compound had activity against the plant pathogen Colletotrichum gloeosporioides, assayed by the paper disk diffusion method (42.7% inhibition, 0.1 mg disk −1 ) and by the microdilution assay (1.25 g L −1 ). Our results reveal the potential of the actinobacteria from the Amazon rhizospheric soils as biocontrol agents as well as producers of new compounds with antifungal activity. Thus, this work constitutes a step forward in the development of the biotechnology of actinobacteria in the production of compounds of agronomic interest. Abstract : A novel antifungal compound produced by an Amazon actinobacteria ( Streptomyces morookaense AM25) and its in vitro activity.